Evaluation of crop effects on runoff and washout of soil from the surface of agricultural land - Podhrázská, Jana; Uhlířová, Jana; Hejduk, Stanislav (Soil and water research, 2009)
Measurements of the runoff intensity (i.e. its volume and amounts of washed out soil particles) were performed on experimental plots with the slope gradient of 5° within the period of 2004–2008. Experimental plots were covered with different types of crops: crops with wide rows (maize, potatoes), no row crops (cereals) and permanent grasslands (both extensively and intensively managed). The main objective of this study was to quantify the effect of individual crops on the reduction of runoff and erosion transport (i.e. washout) of soil from the surface of agricultural land. Data measured on individual experimental plots were compared with control, which was represented by a plot of bare soil. As compared with control, markedly reduced values of both runoff and washout (86 and 99%, respectively) were measured on plots covered with cereals within the study period. In maize stands, the corresponding values were 21 and 11%, respectively. The obtained results may support and contribute to the proposal of organisational soil protection measures and their implementation on agricultural land. In erosion-endangered localities an appropriate selection of individual crops represents an important tool, which can significantly support other protective measures, especially those of technical character.